Implementasi Silent Demonstration pada Open Learning Environments (OLEs) sebagai Penguatan Keterampilan 4C - Munawaroh, Diah Ambarumi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
The purpose of this study is to describe the implementation of Silent Demonstration in Open Learning Environments and how these activities can integrate students to critical thinking, creative, communication, and collaboration in social studies subjects. The method used by the researcher is a phenomenological qualitative approach by describing the behavior, responses, actions of individuals and groups in the form of words and language, naturally (naturally). Data collection techniques through observations in grades VIII G and VIII H, in-depth interviews with subject teachers and group leaders of 14 students and documentation during the research. The research results are that the implementation of silent demonstrations in OLEs attracts students' attention through observations in understanding production, consumption and distribution activities so that learning objectives are achieved. This learning activity integrates integrated skills between Silent Demonstration which attracts students' attention through observation and Open Learning Environments (OLEs) which presents the context of a natural resource perspective from the environment.to build multiple points of view through tools/media as an effort to strengthen 4C learning (critical thinking, creative, collaborative and communicative)Â Â